Public Perceptions and Knowledge of the Ebola Virus, Willingness to Vaccinate, and Likely Behavioral Responses to an Outbreak. (14th June 2016) - Petrie, Keith J; Faasse, Kate; Thomas, Mark G
Abstract: Objective: We examined public perceptions of the risk of an Ebola outbreak, knowledge about transmission, and the factors associated with planned protective behavior, including willingness to vaccinate. Methods: We conducted a cross-sectional telephone survey using random digit dialing of 750 members of the New Zealand public between February 12 and 19, 2015. Results: Most of the sample (72%) reported that they had been following news of the outbreak closely and 28% were concerned that there would be a large outbreak in New Zealand. High rates of planned protective behavior, in terms of avoiding contact with other people, were reported, with 23% reporting they would avoid going to work, 49% reporting they would avoid using public transport, 42% reporting they would avoid sending children to school, and 52% reporting they would avoid public events. A younger age, a higher concern, and lower confidence in the ability of hospitals to contain the outbreak were significantly associated with both a greater willingness to vaccinate and a larger number of protective behaviors. Conclusions: An Ebola outbreak would have large social and economic consequences owing to the large proportion of the population who intended to avoid social contact in order to protect their health. ( Disaster Med Public Health Preparedness . 2016;10:674–680)